Incipient caries: an early intervention approach - John, Mini K.; Babu, Anulekh; Gopinathan, Anupama S. (International Journal Of Community Medicine And Public Health, 2017)
Dental caries is an irreversible microbial disease of the calcified tissues of the teeth, characterized by demineralization of the inorganic portion and destruction of the organic substance of the tooth, which often leads to cavitation (Shafer-1993). Organic acids produced as a by-product of fermentable carbohydrate metabolism plays a key role in the disease. The caries process is a continuous, involving various cycles of demineralization and remineralization. Demineralization begins at the atomic level on the crystal surface in enamel or dentine and can continue to cavitation. However currently there are many treatment modalities to intervene this continuing process, to arrest or reverse the progress of the lesion. Remineralization is the natural repair process for non-cavitated or incipient carious lesion.